2021
DOI: 10.1002/open.202100221
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Antibacterial Activity, and Catalytic Application of Magnetic Graphene Oxide‐Fucoidan in the Synthesis of 1,4‐Dihydropyridines and Polyhydroquinolines

Abstract: Polymer‐coated magnetic nanoparticles are emerging as a useful tool for a variety of applications, including catalysis. In the present study, fucoidan‐coated magnetic graphene oxide was synthesized using a natural sulfated polysaccharide. The prepared BaFe 12 O 19 @GO@Fu (Fu=fucoidan, GO=graphene oxide) was characterized using Fourier‐transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy‐dispersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Since then, the antitubercular properties of other DHP derivatives have been reported by many other researchers ( Trivedi et al, 2011 ; Desai et al, 2015 ; Zandhaghighi et al, 2017 ; Venugopala et al, 2021 ). DHPs have been also evaluated as antimicrobials against other pathogenic bacteria including S. aureus ( Ceviz et al, 1997 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Nosrati et al, 2021 ), E. coli ( Murthy et al, 2012 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Pseudomonas aeruginosa ( Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Vibrio cholerae ( Lavanya et al, 2021 ) and Klebsiella pneumoniae ( Murthy et al, 2012 ); but also against parasites ( Núñez-Vergara et al, 1997 ; Palit and Ali, 2008 ; Reimao et al, 2010 ; Pollo et al, 2017 ; Jeddi et al, 2021 ) and fungi ( Chhillar et al, 2006 ; Jezikova et al, 2017 ; Ahamed et al, 2018 ). This class of molecules have been also studied as inhibitors of bacterial transmembrane efflux pumps, acting thereby as enhancers of the action of conventional antibiotics ( Lentz et al, 2016 , 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the antitubercular properties of other DHP derivatives have been reported by many other researchers ( Trivedi et al, 2011 ; Desai et al, 2015 ; Zandhaghighi et al, 2017 ; Venugopala et al, 2021 ). DHPs have been also evaluated as antimicrobials against other pathogenic bacteria including S. aureus ( Ceviz et al, 1997 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Nosrati et al, 2021 ), E. coli ( Murthy et al, 2012 ; Olejnikova et al, 2014 ; Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Pseudomonas aeruginosa ( Mahmoodi et al, 2015 ; Nkosi et al, 2016 ; Ahamed et al, 2018 ), Vibrio cholerae ( Lavanya et al, 2021 ) and Klebsiella pneumoniae ( Murthy et al, 2012 ); but also against parasites ( Núñez-Vergara et al, 1997 ; Palit and Ali, 2008 ; Reimao et al, 2010 ; Pollo et al, 2017 ; Jeddi et al, 2021 ) and fungi ( Chhillar et al, 2006 ; Jezikova et al, 2017 ; Ahamed et al, 2018 ). This class of molecules have been also studied as inhibitors of bacterial transmembrane efflux pumps, acting thereby as enhancers of the action of conventional antibiotics ( Lentz et al, 2016 , 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[38] In recent years, Nosrati et al synthesized number of polyhydroquinoline derivatives (c) and investigated their antimicrobial activities which exhibit good activity against gram-positive bacteria S. aures. [39] Similarly, Zainab et al reported various compounds based on PHQ nucleus, which exhibit significant antibacterial activity against Escherichia coli (gram-negative bacterium)…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Nosrati et al . synthesized number of polyhydroquinoline derivatives ( c ) and investigated their antimicrobial activities which exhibit good activity against gram‐positive bacteria S. aures [39] . Similarly, Zainab et al .…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our work on the synthesis of heterocyclic structures 22 24 , we reported the synthesis of a new efficient magnetite-base catalytic system, CuFe 2 O 4 @SiO 2 @l-arginine@Cu, along with its application in an approach to 1,2,3-triazole derivatives. The procedure uses phenylacetylene as an alkyne, sodium azide, and various alkyl halides as the other component to form triazoles.…”
Section: Introductionmentioning
confidence: 99%